(untitled) (Agro Productividad, 2021)
Objective: To describe the use of renewable energies in companies in the agricultural sector in order to associate their use to competitiveness variables and to determine if their incorporation has an impact on the competitive performance of the companies. Design/Methodology/Approach: An instrument was designed aimed at managers and owners of companies in the agricultural sector based on the theory of industrial organization and competitiveness. The information was coded, and association tests as well as comparative cluster analysis were performed. Results: The use of renewable energy by the companies addresses economic and commercial strategies. Of the twelve competitiveness variables used to compare companies, nine were linked to the use of renewable energies. The companies using renewable energy demonstrated superior results in competitiveness. Study Limitations/Implications: The results are applicable to companies in the agricultural sector within the region analyzed. Financial and energy consumption variables should be considered if the method of analysis is to be replicated. Findings/Conclusions: The use of renewable energy is a strategic behavior that allows companies to improve their market position. Companies that use renewable energy as a strategic behavior are more competitive.